2013
DOI: 10.1007/s13277-013-0844-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of DNA repair genes XPD, XRCC1, and OGG1, and lung adenocarcinoma susceptibility in Chinese population

Abstract: Lung adenocarcinoma (ADC) is one of the major histological types of lung cancer. Genetic polymorphism in DNA repair genes and lung ADC susceptibility is well documented. In this case-control study, the association between the polymorphic sites of DNA repair genes XPD-751, XRCC1-399, and OGG1-326, and lung ADC susceptibility in ethnic Han Chinese population has been investigated. Genomic DNA was isolated from the peripheral blood of 201 healthy controls and 82 lung ADC patients from the people of Hunan Province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This suggests that individuals with the Cys/Cys polymorphism may be more susceptible to oxidative stress‐induced pathologies. The frequency of known variants within all human populations ranges from 22 to 59% for Ser/Cys and 3–33% for Cys/Cys (Alanazi et al, ; Curtin et al, ; Gangwar, Manchanda, & Mittal, ; Gharib, Dabour, Etewa, & Fouad, ; Ouyang et al, ; Parine et al, ; Zhang et al, ). Thus, OGG1 polymorphisms, as well as environmental factors affecting OGG1 protein levels, such as cadmium exposure (Youn et al, ), may be determinants of risk for not only FASD, but also other pathologies involving enhanced oxidative stress in utero , such as structural birth defects and in utero origins of cancer (Figure ).…”
Section: Dna Repairmentioning
confidence: 99%
“…This suggests that individuals with the Cys/Cys polymorphism may be more susceptible to oxidative stress‐induced pathologies. The frequency of known variants within all human populations ranges from 22 to 59% for Ser/Cys and 3–33% for Cys/Cys (Alanazi et al, ; Curtin et al, ; Gangwar, Manchanda, & Mittal, ; Gharib, Dabour, Etewa, & Fouad, ; Ouyang et al, ; Parine et al, ; Zhang et al, ). Thus, OGG1 polymorphisms, as well as environmental factors affecting OGG1 protein levels, such as cadmium exposure (Youn et al, ), may be determinants of risk for not only FASD, but also other pathologies involving enhanced oxidative stress in utero , such as structural birth defects and in utero origins of cancer (Figure ).…”
Section: Dna Repairmentioning
confidence: 99%
“…The xeroderma pigmentosum complementation group D (XPD) and xeroderma pigmentosum complementation group C (XPC) repair bulky DNA adducts. Experimental reports have suggested that XPD Lys751Gln (Lys Gln) polymorphisms may increase susceptibility to esophageal cancer, lung cancer, bladder cancer and other digestive system cancers (10)(11)(12)(13)(14), and many molecular epidemiological studies have investigated the relationship between XPD Lys751Gln polymorphisms and the predisposition to esophageal cancer. However, the results of these reports remain inconclusive and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been indicated that genetic factors play key functions in contributing to lung cancer susceptibility and influencing the prognosis of patients (Viktorsson et al, 2005;Yin et al, 2009a,b). The human X-ray repair cross-complementing group 1 (XRCC1) gene has been regarded as one of the most important candidate genes for influencing the development of lung cancer (Hao et al, 2006;Giachino et al, 2007;Lopez-Cima et al, 2007;Sreeja et al, 2008;Chang et al, 2009;Kalikaki et al, 2009;Wang et al, 2009Wang et al, , 2014aYin et al, 2009a,b;Butkiewicz et al, 2011;Huang et al, 2011Huang et al, , 2013Li et al, 2011Li et al, , 2012Li et al, , 2013Li et al, , 2014Perez-Morales et al, 2011;Qian et al, 2011;Rybarova et al, 2011;Chen et al, 2012;Cui et al, 2012;Dai et al, 2012;Karkucak et al, 2012;Ke et al, 2012;Guo et al, 2013a,b;Letkova et al, 2013;Natukula et al, 2013;Ouyang et al, 2013;Sun et al, 2013;Wu et al, 2013;Zhang et al, 2014a,b). It has been suggested that the XRCC1 proteins play important roles in DNA base excision repair (BER) pathway which affected the etiology of lung cancer.…”
Section: Introductionmentioning
confidence: 99%